Molecular Detection of Carbapenemase-Encoding Genes in Multidrug-Resistant Acinetobacter baumannii Clinical Isolates in South Africa - Yaw Adjei Anane; Teke Apalata; Sandeep Vasaikar; Grace Emily Okuthe; Sandile Songca (International Journal of Microbiology)
Introduction. Carbapenem-resistant Acinetobacter baumannii has been responsible for an increasing number of hospital-acquired infections globally. The study investigated the prevalence of carbapenemase-encoding genes in clinical multidrug-resistant A. baumannii strains. Materials and Methods. A total of 100 nonduplicate multidrug-resistant A. baumannii strains were cultured from clinical samples obtained from healthcare facilities in the O. R. Tambo district. The strains were confirmed by detecting the intrinsic blaOXA-51-like gene. Antimicrobial susceptibility testing was performed by VITEK® 2 and autoSCAN-4 systems. The MIC of imipenem and meropenem was rechecked by E-test. Colistin MIC was confirmed by the broth microdilution method. Real-time PCR was performed to investigate the presence of carbapenemase-encoding genes. Results. Most strains showed high resistance rates (>80%) to the antibiotics tested. Resistance to amikacin, tetracycline, and tigecycline were 50%, 64%, and 48%, respectively. All strains were fully susceptible to colistin. The blaOXA-51-like was detected in all strains whilst blaOXA-23-like, blaOXA-58-like, blaOXA-24-like, blaIMP-1, blaVIM, and blaNDM-1 were found in 70%, 8%, 5%, 4%, 3%, and 2% of strains, respectively. None of the tested strains harboured the genes blaSIM and blaAmpC. The coexistence of blaOXA-23-like, and blaIMP-1 or blaOXA-58-like was detected in 1% and 2% strains, respectively. A distinct feature of our findings was the coharbouring of the genes blaOXA-23-like, blaOXA-58-like, and blaIMP-1 in 2% strains, and this is the first report in the Eastern Cape Province, South Africa. The intI1 was carried in 80% of tested strains whilst ISAba1/blaOXA-51-like and ISAba1/blaOXA-23-like were detected in 15% and 40% of the strains, respectively. The detection of blaOXA-23-like, ISAba1/blaOXA-51-like, ISAba1/blaOXA-23-like, and blaOXA-23-like, blaOXA-58-like, and blaIMP-1 carbapenemases in strains had a significant effect on both imipenem and meropenem MICs. Conclusions. Results showed a high level of oxacillinases producing A. baumannii circulating in our study setting, highlighting the need for local molecular surveillance to inform appropriate management and prevention strategies.